If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + 1) = 2(5 + -1x) Reorder the terms: -1(1 + x) = 2(5 + -1x) (1 * -1 + x * -1) = 2(5 + -1x) (-1 + -1x) = 2(5 + -1x) -1 + -1x = (5 * 2 + -1x * 2) -1 + -1x = (10 + -2x) Solving -1 + -1x = 10 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -1 + -1x + 2x = 10 + -2x + 2x Combine like terms: -1x + 2x = 1x -1 + 1x = 10 + -2x + 2x Combine like terms: -2x + 2x = 0 -1 + 1x = 10 + 0 -1 + 1x = 10 Add '1' to each side of the equation. -1 + 1 + 1x = 10 + 1 Combine like terms: -1 + 1 = 0 0 + 1x = 10 + 1 1x = 10 + 1 Combine like terms: 10 + 1 = 11 1x = 11 Divide each side by '1'. x = 11 Simplifying x = 11
| -12=2+7v | | 49.8-6-18.8= | | 2*cos(4x)=0 | | x^2-2x-15624=0 | | 9a-4(-5a-1)= | | 0.3y^2+0.7y^2-0.2y^2= | | 72=90-x | | 8-3(6-6x)= | | .4x-.9y=.7 | | 9=2(4-x)+7 | | 3x(4x+3)= | | 13x-7=42+6x | | 12r+36=2r+10-3r | | (x-9)(x-9)=0 | | (8a+6)2=34 | | 13-8y=5y+2 | | 2c+3=4c-4 | | 150=4.5t | | (18-7)+1=-9 | | 20+2n=52 | | 81-18s+s^2=0 | | -8+10=12 | | 2/7=j+3 | | -29=7n-8 | | -2x-5=10 | | 5s^7-7s-35x+49=0 | | (6)(-4)(-3)= | | w^2-4w=-21 | | 3x+2iy=6+10i | | 27x^2-3x+4=0 | | 21x+12=6x-3 | | 2-(3)x=4 |